When calls the heart [videorecording (DVD)] - Landon, Michael, 1964-; Grace, Maggie, 1983-; Amell, Stephen, 1981-; Drayton, Poppy; Sharman, Daniel; Lunghi, Cherie, 1952-; Villiers, Christopher; Smart, Jean; Loughlin, Lori; Oke, Janette, 1935- (Millennium Entertainment, 2013)
Young teacher Elizabeth Thatcher trades high society life for a classroom on the prairie, determined to prove she is brave enough to live on her own. She learns through her aunt's secret diary that she had been a pioneer woman herself, and uses it as a guide to embark on her own adventures.